The community structure of zooplankton in Bojonegara coastal waters, Banten Bay, Indonesia - Sunarwati Srimariana Endang; Maria Diandra Rahardjo Alexandra; Sulistiono Sulistiono; Sidabutar Tumpak (BIO Web of Conferences)
Bojonegara coastal waters, located in an area experiencing significant industrial expansion, are under increasing environmental stress. This study aims to analyze the zooplankton community structure in these waters. The research, conducted from January to October 2020, involved six stations across river, estuary, and sea areas. Data analysis covered various ecological indices, including abundance, diversity, evenness, dominance, principal component analysis, and Bray-Curtis similarity index. Environmental parameters such as temperature, transparency, turbidity, salinity, pH, dissolved oxygen, nitrate, and phosphate were also measured. The study identified zooplankton from 10 different classes, comprising Malacostraca (16 genera), Rotifera (6 genera), Ciliata (4 genera), Rhizopoda (2 genera), and one genus each from Bivalvia, Gastropoda, Polychaeta, Sagittoidea, Sarcodina, and Urochordata. Malacostraca and Ciliata were the dominant groups. Zooplankton abundance, as well as diversity (H’), evenness (E), and dominance (C) indices, varied between 2.8x104 and 9.9x104 ind/L, 1.061 to 1.646, 0.713 to 0.771, and 0.282 to 0.433, respectively. The zooplankton community structure indicated that Bojonegara waters are experiencing mild environmental stress, with temperature and nitrate levels being key factors affecting zooplankton abundance.